Implementasi Kebijakan Pengadaan Tanah untuk Kepentingan Umum di Jakarta Utara - Mulyadi, Mohammad (Jurnal Aspirasi, 2017)
The research based on the assumptions on the phenomena used as the study object is intended to examine and to analyze the nature of land policy in North Jakarta Municipal Administration is designated for the public interest. Referring to the purpose of the research achieved, this study aims at: 1) Identifying and describing the form of interpretation of land acquisition for the public interest; 2) Identifying and explaining the form of land procurement organization for the public interest; 3). Identifying and explaining the form of land acquisition for public purposes. This study used a qualitative approach, with data collection conducted prioritizing the views of informants. The results of land acquisition research for public interest were conducted with the help of land procurement committee. One duty of the committee is to conduct research on the legal status of the right to the land that will be waived or claimed and supporting documents as well as to undertake inventory over land including buildings or standing structures built upon it.Penelitian yang disusun berdasarkan asumsi terhadap fenomena yang dijadikan objek kajian dimaksudkan untuk mengkaji dan menganalisis bagaimana kebijakan pertanahan di Pemerintah Kota Adminsitrasi Jakarta Utara yang diperuntukkan bagi kepentingan umum. Merujuk pada maksud penelitian yang dicapai, maka penelitian ini bertujuan untuk: 1) Mengetahui dan menjelaskan bagaimana bentuk interpretasi pengadaan tanah untuk kepentingan umum; 2) Mengetahui dan menjelaskan bagaimana bentuk pengorganisasian pengadaan tanah untuk kepentingan umum; 3) Mengetahui dan menjelaskan bagaimana bentuk pelaksanaan pengadaan tanah untuk kepentingan umum. Penelitian ini menggunakan pendekatan kualitatif, dengan pengumpulan data dilakukan mengutamakan pandangan informan. Hasil penelitian pengadaan tanah untuk kepentingan umum dilakukan dengan bantuan panitia pengadaan tanah. Panitia pengadaan tanah ini bertugas untuk mengadakan penelitian mengenai status hukum tanah yang haknya akan dilepaskan atau diserahkan dan dokumen yang mendukungnya serta melakukan inventarisasi atas tanah dan bangunan yang berdiri di atas tanah tersebut.